HAND GESTURE RECOGNITION USING MACHINE LEARNING - Mr. Pratik Annaramchandra Yadav; Mr. R. S. Patil (International Journal of Innovations in Engineering Research and Technology, 2023)
In order to offer new possibilities to interact with machine and to design more natural and more intuitive interactions with computing machines, this research aims at the automatic interpretation of gestures based on computer vision. One such technique can be used for detecting and understanding various human gestures as it would make the human-machine communication effective. This could make the conventional input devices like touchscreens, mouse pad, and keyboards redundant. In this project we will design a hand gesture recognition system which will perform defined task. Here we are using classroom as an application. Instead of classroom any other applications can be also used.